2018
DOI: 10.1186/s12974-018-1292-4
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation contributes to perioperative neurocognitive disorders in mice

Abstract: BackgroundThe complement system plays an important role in many neurological disorders.Complement modulation, including C3/C3a receptor signaling, shows promising therapeutic effects on cognition and neurodegeneration. Yet, the implications for this pathway in perioperative neurocognitive disorders (PND) are not well established. Here, we evaluated the possible role for C3/C3a receptor signaling after orthopedic surgery using an established mouse model of PND.MethodsA stabilized tibial fracture surgery was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 49 publications
(82 reference statements)
4
47
0
Order By: Relevance
“…Interestingly, C3 levels in our data were increased in GFAP+ astrocytes. Astrocytic C3 production may modulate synaptic density, as observed in models of Alzheimer's disease (Lian et al, 2015(Lian et al, , 2016Luchena et al, 2018), amyotrophic lateral sclerosis (Heurich et al, 2011), perioperative neurocognitive disorder (Xiong et al, 2018) and diabetes (Zhao et al, 2018). We now show that there may be a similar phenomenon in the mIA model of schizophrenia.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, C3 levels in our data were increased in GFAP+ astrocytes. Astrocytic C3 production may modulate synaptic density, as observed in models of Alzheimer's disease (Lian et al, 2015(Lian et al, , 2016Luchena et al, 2018), amyotrophic lateral sclerosis (Heurich et al, 2011), perioperative neurocognitive disorder (Xiong et al, 2018) and diabetes (Zhao et al, 2018). We now show that there may be a similar phenomenon in the mIA model of schizophrenia.…”
Section: Discussionsupporting
confidence: 61%
“…And the immunity plays an important role in maintaining the function of the blood-brain barrier. Peripheral surgery may disrupt the BBB via complement activation and pro-inflammatory cytokines, such as TNF-α and high mobility group box-1 (HMGB1), which promotes brain inflammation [ 50 , 51 ]. Furthermore, BBB disruption facilitates the migration of macrophages into the brain, and the hippocampal recruitment of macrophages is necessary for neuroinflammation and memory dysfunction, inducing cognitive decline following surgery [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis on peptides that showed trend-level signi cance with q < 0.25 identi ed a signi cant role for the complement and coagulations factors pathway(s). The hypothesis that complement plays a role in perioperative neurocognitive disorders aligns with current animal models of surgery-induced neuroin ammation and cognitive decline [62]. Complement regulates brain development and homeostasis by driving microglial synaptic phagocytosis [63], and in murine models, complement-dependent synaptic pruning is critical for optimizing cognitive performance by reducing excessive synapse numbers that can cause epilepsy [64,65].…”
Section: Discussionmentioning
confidence: 91%
“…A role for complement in perioperative neurocognitive disorders would t the theory that these disorders are driven by neuroin ammation [1,69]. Indeed, murine model studies have shown that complement C3 levels, an initiator of the complement cascade, and levels of the receptor for its cleavage product (C3aR) are elevated after orthopedic surgery, and these increases have been shown to contribute to cognitive dysfunction in mouse POCD models [62]. Similarly, elevated baseline CSF C3 levels have been associated with higher rates of postoperative delirium in human patients [70], and critically-ill patients with delirium have been found to exhibit upregulated CSF complement levels [71].…”
Section: Discussionmentioning
confidence: 99%